Perinatal and one‐year outcomes of non‐immune hydrops fetalis by etiology and age at diagnosis. Issue 4 (29th December 2015) - Ota, Shiyo; Sahara, Jun; Mabuchi, Aki; Yamamoto, Ryo; Ishii, Keisuke; Mitsuda, Nobuaki
Abstract: Aim: The prognosis for non‐immune hydrops fetalis (NIHF) is still poor despite progress in perinatal care. We have examined perinatal and 1‐year outcomes for NIHF in relation to gestational age at diagnosis and underlying etiology in order to identify predictors of mortality. Methods: A retrospective review was conducted of 92 pregnancies with NIHF managed in hospital between 2000 and 2012. The gestational age at diagnosis, etiology, perinatal outcome, and 1‐year outcome were recorded, and their associations assessed. Results: A total of 41 of 92 cases (45%) resulted in fetal death, 33 patients (36%) survived to 1 year, but only 15 of the 33 survivors were developmentally intact. Aneuploidy was the most common cause of NIHF (27%; 25/92). Of the 34 patients who were diagnosed before 22 weeks, 29 fetuses (85%) died, and four (12%) survived to 1 year without developmental delay. Meanwhile, of the 26 patients diagnosed after 30 weeks, 18 (69%) survived to 1 year. Of those 18, seven (27%) were developmentally intact. Approximately half of the pregnancies with cardiac anomalies (8/13) resulted in intrauterine fetal death (IUFD) or early neonatal death. Aneuploidy was associated with a high frequency of IUFD, and of the remaining five surviving newborns, three had developmental delay. Conclusion: The prognosis for NIHF differs according to underlying etiology and gestational age at diagnosis. NIHF diagnosed early in gestation is associated with poor outcome. Knowledge of the primary etiology is important for counseling and therapy.